Transformation of new media in Aswaja al-Nahdliyyah da'wah: Strategies and challenges in the contestation of religious authority in Indonesia - Mudhofi, M.; Karim, Abdul (Islamic Communication Journal, 2024)
The presence of new media has caused contestation between religious authorities in Islamic society. However, what stands out most is that new media has given birth to new spaces where every individual and group, including those who are often considered splinter, are free to present themselves and their identities in public. This research aims to examine the specific challenges Aswaja Al-Nahdliyyah faces in maintaining doctrinal purity, combating misinformation, and navigating the complexities of digital communications. This research uses qualitative research in an interpretive paradigm, utilizing online data from the NU Website and YouTube channels.  The narrative of Ahl al-Sunnah wa al-Jama'ah al-Nahdliyyah is very important to be promoted and mainstreamed, so that it is increasingly strengthened into a complete narrative which is called the new cultural environment of Ahl al-Sunnah wa al-Jama'ah al-Nahdliyyah. This new environment can be seen from the digitization of Nahdlatul Ulama (NU) figures and the yellow books (turats) taught at NU Islamic boarding schools. This digitalization seeks to show that new religious spaces in the online world must be under the control of authorized religious figures.*****Kehadiran media baru telah menimbulkan kontestasi antar otoritas agama dalam masyarakat Islam. Namun yang paling menonjol adalah media baru telah melahirkan ruang-ruang baru di mana setiap individu dan kelompok, termasuk mereka yang kerap dianggap pecahan (sempalan), bebas menampilkan diri dan identitasnya di depan publik. Penelitian ini bertujuan untuk mengkaji tantangan spesifik yang dihadapi Aswaja Al-Nahdliyyah dalam menjaga kemurnian doktrin, memerangi misinformasi, dan menavigasi kompleksitas komunikasi digital. Penelitian ini menggunakan penelitian kualitatif dengan paradigma interpretatif, memanfaatkan data online dari Website NU dan channel YouTube.  Narasi Ahl al-Sunnah wa al-Jama'ah al-Nahdliyyah sangat penting untuk dipromosikan dan diarusutamakan, agar semakin kuat menjadi sebuah narasi utuh yang disebut dengan lingkungan budaya baru Ahl al-Sunnah wa al- Jama'ah al-Nahdliyyah. Lingkungan baru ini terlihat dari digitalisasi tokoh Nahdlatul Ulama (NU) dan kitab kuning (turats) yang diajarkan di pesantren NU. Digitalisasi ini berupaya menunjukkan bahwa ruang keagamaan baru di dunia online harus berada di bawah kendali tokoh agama yang berwenang.